Assessment of Bone Marrow Biopsy and Cytogenetic Findings in Patients with Multiple Myeloma - Ahmet Seyhanlı; Boran Yavuz; Zehra Akşit; Zeynep Yüce; Sermin Özkal; Oğuz Altungöz; Fatih Demirkan; İnci Alacacıoğlu; Güner Hayri Özsan (Turkish Journal of Hematology, 2022)
Objective: Multiple myeloma (MM) is a malignant condition characterized by the accumulation of malignant plasma cells. Although MM remains incurable, the survival of MM patients has improved considerably due to the application of autologous stem cell transplantation, novel agents, and advanced treatment strategies. This study aimed to determine the cytogenetic characterization and bone marrow (BM) features of Turkish patients with MM. Materials and Methods: Eighty-five MM patients were admitted to Dokuz Eylül University Hospital in Turkey. BM samples of these MM patients were subjected to cytogenetic analyses at diagnosis and during therapy as a part of therapeutical and clinical evaluation. A complete cytogenetic study was performed using the G-banding technique. Fluorescence in situ hybridization (FISH) analysis was performed using cytoplasmic immunoglobulin. The degree of BM fibrosis was determined using reticulin histochemical staining. We determined the percentage of BM plasma cells based on the extent of CD38 staining. Results: Eighty-five MM patients were retrospectively identified between 2015 and 2021. The median age was 63 (38-90) years. Of the 85 patients, 60 (70.6%) were male and 25 (29.4%) were female. Seventy-two (84.7%) cases had BM fibrosis at the time of diagnosis. The most common was grade 2 fibrosis, recorded in 35 cases (41.2%). About 72.9% of the patients showed more than 50% plasma cells. FISH analysis indicated the presence of abnormal chromosomes in 37% (32/85) of the patients. The most frequent abnormality was Immunoglobulin heavy-chain (IGH) translocation (21.3%). Conclusion: Subgroup analysis of IGH mutations is crucial in the identification of high-risk MM patients. We believe that our study will contribute to the determination of BM biopsy and cytogenetic features of MM patients in our country.